2021
DOI: 10.1111/jcmm.17104
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome modulates NLRP3 inflammasome‐mediated neuroinflammation under cerebral ischaemia and reperfusion conditions

Abstract: Compelling evidence showed that both nucleotide‐binding oligomerization domain‐like receptor family, pyrin domain‐containing protein 3 (NLRP3) inflammasomes and the immunoproteasome participate in neuroinflammatory responses in cerebral ischaemia injury. Moreover, inhibition of either NLRP3 inflammasomes or the immunoproteasome attenuates both neuroinflammation and neurological deterioration during ischaemic stroke. However, the underlying mechanism between the immunoproteasome and NLRP3 inflammasomes under is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…393 An in vitro study revealed that treatment modulating the immunoproteasome/NF-κB/NLRP3 inflammasome signaling axis could work against hypoxia and ischemia, as well as prevent apoptosis. 394 Therefore, inhibition of NLRP3 inflammasome formation could possibly attenuate ischemic stroke inflammatory processes and limit cell death.…”
Section: Pathophysiology and Signaling Pathways Involved In Ischemic ...mentioning
confidence: 99%
“…393 An in vitro study revealed that treatment modulating the immunoproteasome/NF-κB/NLRP3 inflammasome signaling axis could work against hypoxia and ischemia, as well as prevent apoptosis. 394 Therefore, inhibition of NLRP3 inflammasome formation could possibly attenuate ischemic stroke inflammatory processes and limit cell death.…”
Section: Pathophysiology and Signaling Pathways Involved In Ischemic ...mentioning
confidence: 99%
“…Post-mortem analysis of stroke patient’s brains showed higher expression of NLRP3 and caspase-1 along with IL-1 and IL-18 . Similarly, a recent study has demonstrated a 4-fold increase in NLRP3 protein levels in rat brains subjected to ischemic stroke . The NLRP3 expression was mainly observed in the cytoplasm of microglia astrocytes and neurons in the area surrounding the infarct core .…”
Section: Role Of Nlrp3 In Strokementioning
confidence: 94%
“…Similarly, a recent study has demonstrated a 4-fold increase in NLRP3 protein levels in rat brains subjected to ischemic stroke . The NLRP3 expression was mainly observed in the cytoplasm of microglia astrocytes and neurons in the area surrounding the infarct core . Franke et al also found that NLRP3 and other NLRP3 inflammasome-related genes were upregulated within 24 h after stroke .…”
Section: Role Of Nlrp3 In Strokementioning
confidence: 95%
“…BAY 11-7082 suppresses the phosphorylation of IκBα and NF-κB translocation to the nucleus induced by TNF-α, thereby suppressing NLRP3 inflammasome activation ( 122 ). Following oxygen-glucose deprivation and re-oxygenation, BAY 11-7082 decreases the levels of the NLRP3 inflammasome and cleaved caspase-1 protein in BV2 microglial cells, presenting a pharmacological effect in stroke ( 123 ). Moreover, chronic cold stress activates the microglia, causing neuroinflammation that can be significantly inhibited by BAY 11-7082 by targeting the GABA-induced NLRP3 inflammasome ( 124 ).…”
Section: Inhibitors Of the Nlrp3 Inflammasome Pathwaymentioning
confidence: 99%